Minyak Buah Merah Meningkatkan Aktivitas Proliferasi Limfosit Limpa Mencit Setelah Infeksi Listeria Monocytogenes - Wahyuniari, Ika; HNE Soesatyo, Marsetyawan; Ghufron, Muhammad; -, Yustina; Ari Sumiwi, Andwi; Wiryawan, Sri (Jurnal Veteriner; Vol 10 No 3 (2009))
The success of individual in keeping healthy from infectious disease is closely related to the ability oftheir body immune responses againts infectious agents. It is reported that one way to increase the immuneresponses is by system to antioxidant. Red fruit oil contains carotenoid and tocoferol that function asantioxidant. This study was aimed at investigating the effect of red fruit oil on spleen lymphocyteproliferation in mice infected with Listeria monocytogenes. Sixty female Balb/c mice were used in thisstudy. The animals were randomly selected and divided into five groups, each group were 12 mice. The firstand second groups received aquadest only, whereas the third, fourth, and fifth groups received red fruit oilwith different doses, ie. 0.3, 0.6, and 1.2 mL/kbBW/day, respectively. Lymphocyte proliferation activitieswere tested by using 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay method.Lymphocyte proliferation assay demonstrated that there was significant difference between the groupswith red fruit oil and aquadest, started at day 2 post-infection. The optical density (OD) values recorded atday 3 in groups I, II, III, IV, and V were 0.769 ± 0.025, 0.904 ± 0.048, 1.110 ± 0.020, 1.021 ± 0.033, 0.979 ±0.002, respectively. The highest optical density (OD), ie. 1.194 ± 0.032, occurred at day 6 after receiving 0,3mL/kgBW/day. In conclusion, red fruit oil could increase lymphocyte proliferation.
Keywords: Red fruit oil, Listeria monocytogenes, Lymphocyte proliferation, mice